What remains after transient global amnesia (TGA)?: an ultra‐high field 7 T magnetic resonance imaging study of the hippocampus - Paech, Daniel; Kuder, Tristan Anselm; Roßmanith, Christina; Griebe, Martin; Eisele, Philipp; Platten, Michael; Ladd, Mark E.; Schlemmer, Heinz-Peter; Gass, Achim; Szabo, Kristina (European journal of neurology, 2020)
Background and purpose - The aim was to study whether ultra‐high field 7 T magnetic resonance imaging (MRI) can demonstrate chronic focal defects in the hippocampus corresponding to the former acute diffusion‐weighted imaging (DWI) lesions and to assess chronic T2‐hyperintense hippocampal lesion load in transient global amnesia (TGA) patients.